Metal removal from water treatment plant sludge overflow using zeolite adsorption - 353281 Ikmalzatul Abdullah; Azmi Aris, supervisor; Fakulti Kejuruteraan Awam (2009)
Project Paper (Sarjana Muda Kejuruteraan (Awam - Alam Sekitar)) - Universiti Teknologi Malaysia, 2009